HUBUNGAN ASUPAN MAKANAN DENGAN IMT (INDEKS MASSA TUBUH) ATLET SEPAKBOLA PERSEKA PATI - Alvin Fitra Alvin Rahmana; Anies Setiowati (Sports Collaboration Journal, 2023)
An athlete's food intake must meet all the nutrients the body needs to replace the energy lost due to daily activities, especially training. Adequacy of nutritional needs can be seen from a person's nutritional status. This study aims to determine the relationship between the intake of nutrients (protein, carbohydrates and fat) with the Body Mass Index (BMI) of Perseka Pati football athletes. This study uses a descriptive correlation method. The subjects in this study were 15 athletes using a purposive sampling technique. Instruments in this study included 24-hour recall and the Nutrisurvey application to determine nutrient intake, body scales to calculate body weight, microtoice to measure height and the BMI formula to calculate Body Mass Index. Data were analyzed using a descriptive test to describe the characteristics of the respondents and Spearman's test to determine the relationship between the variables of nutrient intake and nutritional status. The results of this study were that there was no relationship between carbohydrate intake p-value = 0.07, protein intake p-value = 0.13 and fat intake p-value = 0.50 with BMI. There is no relationship between food intake (protein, carbohydrates and fat) with the BMI of Perseka Pati football athletes Abstrak Asupan makanan seorang atlet harus memenuhi semua zat gizi yang dibutuhkan oleh tubuh untuk mengganti energi yang hilang dari akibat aktivitas sehari-hari khususnya latihan. Tercukupinya kebutuhan zat gizi dapat dilihat dari status gizi seseorang. Penelitian ini bertujuan untuk mengetahui hubungan asupan zat gizi (protein, karbohidrat dan lemak) dengan Indeks Massa Tubuh (IMT) atlet sepakbola Perseka Pati. Penelitian ini menggunakan metode descriptive correlation. Subjek dalam penelitian ini berjumlah 15 atlet dengan menggunakan teknik purposive sampling. Instrumen dalam penelitian ini antara lain Recall 24 jam dan aplikasi Nutrisurvey untuk mengetahui asupan zat gizi, timbangan badan digunakan untuk menghitung berat badan, microtoice digunakan untuk mengukur tinggi badan serta menggunakan rumus IMT untuk menghitung Indeks Massa Tubuh. Data dianalisis menggunakan uji deskriptif untuk mengetahui gambaran karakteristik responden, uji spearman’s untuk mengetahui hubungan antara variabel asupan zat gizi dengan status gizi. Hasil dari penelitian ini adalah tidak terdapat hubungan antara asupan karbohidrat  nilai p-value = 0,07, asupan protein p-value = 0.13 dan asupan lemak p-value = 0.50 dengan IMT. Tidak terdapat hubungan antara asupan makanan (protein, karbohidrat dan lemak dengan IMT atlet sepakbola Perseka Pati